Podocyte-derived microparticles promote proximal tubule fibrotic signaling via p38 MAPK and CD36. Issue 1 (1st January 2018) - Munkonda, Mercedes N.; Akbari, Shareef; Landry, Chloe; Sun, Suzy; Xiao, Fengxia; Turner, Maddison; Holterman, Chet E.; Nasrallah, Rania; Hébert, Richard L.; Kennedy, Christopher R. J.; Burger, Dylan
ABSTRACT: Tubulointerstitial fibrosis is a hallmark of advanced diabetic kidney disease that is linked to a decline in renal function, however the pathogenic mechanisms are poorly understood. Microparticles (MPs) are 100–1000 nm vesicles shed from injured cells that are implicated in intercellular signalling. Our lab recently observed the formation of MPs from podocytes and their release into urine of animal models of type 1 and 2 diabetes and in humans with type 1 diabetes. The purpose of the present study was to examine the role of podocyte MPs in tubular epithelial cell fibrotic responses. MPs were isolated from the media of differentiated, untreated human podocytes (hPODs) and administered to cultured human proximal tubule epithelial cells (PTECs). Treatment with podocyte MPs increased p38 and Smad3 phosphorylation and expression of the extracellular matrix (ECM) proteins fibronectin and collagen type IV. MP-induced responses were attenuated by co-treatment with the p38 inhibitor SB202190. A transforming growth factor beta (TGF-β) receptor inhibitor (LY2109761) blocked MP-induced Smad3 phosphorylation and ECM protein expression but not p38 phosphorylation suggesting that these responses occurred downstream of p38. Finally, blockade of the class B scavenger receptor CD36 completely abrogated MP-mediated p38 phosphorylation, downstream Smad3 activation and fibronectin/collagen type IV induction. Taken together our results suggest that podocyte MPs interact with proximal tubule cells and induce pro-fibrotic responses. Such interactions may contribute to the development of tubular fibrosis in glomerular disease.